Towards controlling the dissociation probability by light-induced conical intersections - Csehi, András; Halász, Gábor J.; Cederbaum, Lorenz S.; Vibók, Ágnes (Ultrafast imaging of photochemical dynamics, 2016)
Light-induced conical intersections (LICIs) can be formed both by standing or by running laser waves. The position of a LICI is determined by the laser frequency while the laser intensity controls the strength of the nonadiabatic coupling. Recently, it was shown within the LICI framework that linearly chirped laser pulses have an impact on the dissociation dynamics of the D2+ molecule (J. Chem. Phys., 143, 014305, (2015); J. Chem. Phys., 144, 074309, (2016)). In this work we exploit this finding and perform calculations using chirped laser pulses in which the time dependence of the laser frequency is designed so as to force the LICI to move together with the field-free vibrational wave packet as much as possible. Since nonadiabaticity is strongest in the vicinity of the conical intersection, this is the first step towards controlling the dissociation process via the LICI. Our showcase example is again the D2+ molecular ion. To demonstrate the impact of the LICIs on the dynamical properties of diatomics, the total dissociation probabilities and the population of the different vibrational levels after the dissociation process are studied and discussed.